Spongy bone deformation mechanisms: Experimental and numerical studies - Chaari, Fahmi; Halgrin, Julien; Markiewicz, Éric; Drazetic, Pascal (European Journal of Computational Mechanics, 2009)
In order to identify the spongy bone's mechanical behaviour, we performed compression tests on cylindrical samples. Experimental results show important dispersions and an unexpected inverse strain rate dependency at low range of loading velocities. The origin of the dispersions can be attributed to the combination of the architecture effect and the mechanical properties variation of the constitutive material. In order to understand the inverse strain rate sensitivity, we used a controlled constitutive material to build new equivalent samples with the spongy bone's architecture. These samples were subjected to compression tests. Numerical simulations of compression tests on the same architecture have been carried out with FE models built from μCt data. The obtained results are compared in term of final sample shape and the evolution of the compression force.